Recent Study on Clinical and Therapeutic Aspects of Giant Fibroids at the Hôpital du Mali about 30 Cases - Mamadou B. Coulibaly; Alassane Traore; Mody A. Camara; Abdrahamane Togo; Adama Sangaré; Issa Ongoiba; Kalba Timbine; Amadou Sidibé; Apérou Guindo; Niani Mounkoro; et al. (Highlights on Medicine and Medical Research Vol. 9, 2021)
Fibroids affect 20% to 25% of reproductive-age women, and black women are 3 to 9 times more likely to develop them. When uterine height approaches or exceeds the navel, we’re talking about giant fibroids. This research was started at the Hôpital du Mali to report on the epidemioclinical and therapeutic aspects of giant fibroids. A descriptive retro-prospective study, conducted in the service of gynecology of the Hôpital du Mali from November 2017 to December 2018 were included in this study, any patients, regardless of their age, having developed a fibroid, the uterine height of the patient reaching or exceeding the umbilicus on physical examination and who were on surgical treatment. We had collected 30 cases of GFs out of the 92 patients who had undergone myomectomies, with a frequency of 32.60%. The age group 25 - 29 years accounted for 46.6% with an average age of 35 years. Housewives represented 50% and nulligravida made up 33% of our patients. Desire to become pregnant was the main reason for consultation in 34.4% of cases. On physical inspection, 46.66 % of the time, the uterine height was between 25 and 29 cm. In 76.64 percent of cases, myomectomy was performed, while hysterectomy was performed in 23.3 %. The size of the nuclei after surgery was over 25 cm in 48.66% of our patients. Conclusion: The giant fibroid (GF) is a common cause of myomectomy. The treatment is either hysterectomy or myomectomy and depends on the indications. Hysterectomy should be reserved for the etiologies: excessive volume of fibroids, postmenopausal women and multiple gravida.